(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2010)
For almost four decades now (since 1972, when the UN held the first specific meeting on the subject), World Environment Day has been celebrated on June 5th. Discussing environmental law and its effective application should be a life project not just for legal professionals, but for every citizen. Brazilians know that there is a Constitution that guarantees their rights and they expect judges and courts to preserve them. Anyone who pollutes the environment is a criminal because environmental legislation qualifies them as such and the Judiciary has the final say on the official interpretation of the rules.